2021
DOI: 10.1101/2021.10.30.466521
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A new tripartite landmark in posterior cingulate cortex

Abstract: Understanding brain structure-function relationships, and their development and evolution, is central to neuroscience research. Here, we show that morphological differences in posterior cingulate cortex (PCC), a hub of functional brain networks, predict individual differences in macroanatomical, microstructural, and functional features of PCC. Manually labeling 4,319 sulci in 552 hemispheres, we discovered a consistently localized shallow cortical indentation (termed the inframarginal sulcus; ifrms) within PCC… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 66 publications
3
16
0
Order By: Relevance
“…After replicating previous findings of a lack of asymmetry in the depth of the inferior frontal sulcus in chimpanzees (Bogart et al 2012), we further showed that there is a larger rightward depth asymmetry for an LPFC tertiary sulcus (pms-p) in chimpanzees compared to humans. Thus, future studies can further explore the functional and cognitive meaning of this asymmetry guided by our shared probabilistic predictions of LPFC sulci (Figure 5), as well as further build from the recent foundation showing the similarities and differences in tertiary sulci across the hominoid clade in ventral temporal (Miller et al 2020), medial prefrontal (Amiez et al, 2019), posterior cingulate (Willbrand et al 2021), and now lateral prefrontal cortices.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…After replicating previous findings of a lack of asymmetry in the depth of the inferior frontal sulcus in chimpanzees (Bogart et al 2012), we further showed that there is a larger rightward depth asymmetry for an LPFC tertiary sulcus (pms-p) in chimpanzees compared to humans. Thus, future studies can further explore the functional and cognitive meaning of this asymmetry guided by our shared probabilistic predictions of LPFC sulci (Figure 5), as well as further build from the recent foundation showing the similarities and differences in tertiary sulci across the hominoid clade in ventral temporal (Miller et al 2020), medial prefrontal (Amiez et al, 2019), posterior cingulate (Willbrand et al 2021), and now lateral prefrontal cortices.…”
Section: Discussionmentioning
confidence: 82%
“…Intriguingly, some tertiary sulci are human-specific, while other tertiary sulci are only present in some, but not all human brains. For example, the mid-fusiform sulcus in ventral temporal cortex and the inframarginal sulcus in posterior cingulate cortex are present in every human brain (Miller et al 2020; Willbrand et al 2021), while the paracingulate sulcus in medial frontal cortex (Paus et al 1996; Fornito et al 2004, 2006, 2008; Amiez et al 2018) and the paraintermediate frontal sulcus in lateral prefrontal cortex (Amiez and Petrides 2007; Voorhies et al 2021) are not. The former three sulci also have been studied in non-human hominoid brains such as chimpanzees (Amiez et al, 2019; Amiez et al 2021; Miller et al 2020; Willbrand et al 2021), while the latter has not.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the many cortical features to study, one of the most prominent is the patterning of the indentations, or sulci. While the majority of sulci are identifiable across individuals, some tertiary sulci that emerge late in gestation are not (Amiez et al, 2019;Chiavaras and Petrides, 2000;Lopez-Persem et al, 2019;Voorhies et al, 2021;Willbrand et al, 2021). For example, the variable presence of the paracingulate sulcus in the anterior cingulate cortex is related to performance on cognitive, motor, and affective tasks in young adults (Amiez et al, 2018;Buda et al, 2011;Fornito et al, 2006Fornito et al, , 2004Huster et al, 2011Huster et al, , 2009Whittle et al, 2009), inhibitory control in children (Borst et al, 2014;Cachia et al, 2014), and in disorders such as schizophrenia (Le Provost et al, 2003;Yücel et al, 2003Yücel et al, , 2002, obsessive-compulsive disorder (Shim et al, 2009), and frontotemporal dementia (Harper et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…( A ) Anatomical locations, normalized to MNI space, of intracranial sEEG depth electrodes targeting the posterior aspect of the cingulate cortex, with the distal contact of probes containing microwires indicated in green. ( B ) Anatomy of human PCC, differentiating dorsal (dPCC) and ventral (vPCC) subregions and demarcating regional sulci following the most recent definitions in PCC (Petrides, 2018; Willbrand et al, 2021). ( C ) Attention/Memory Switch task procedure and example stimuli.…”
Section: Introductionmentioning
confidence: 99%